REHABILITATION AS A TOOL FOR MANAGING THE URBAN ENVIRONMENT - Tursunova Oysha Fakhriddinovna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
Abstract: The article examines the most important aspects and stages of the rehabilitation process in urban environmental management and improving the quality of landscape design. Using a city as an example, it demonstrates the need to develop targeted rehabilitation of the urban environment by improving the urban greening system.